THEORETICAL FOUNDATIONS FOR THE STUDY OF ARTISTIC DETAIL - Lozovoy Aleksey ,F. I. Daminova (International Journal of Literature and Language Studies, 2026)
. This article examines the theoretical foundations of studying artistic detail as an important element of a literary work. The main approaches to defining the concept of artistic detail, its functions, typology, and role in creating artistic imagery are analyzed. Particular attention is paid to the significance of detail in revealing the author's intention, characterizing literary characters, and shaping the artistic space and time of a work. The study emphasizes that artistic detail serves as an essential means of expressing the ideological and aesthetic content of a text and contributes to a deeper understanding of its semantic structure.